Respuesta :
This means which transformation makes the same answer at x = 0
f(x) = 3x + 4
[tex] g(x) = {2}^{x} - 1[/tex]
f(0) = 4
g(0) = 1 - 1 = 0
Which transformation makes 4 = 0?
4 + x = 0 + y
4 - 3 =0 + 1
1 = 1
Option 1 is your answer
f(x) = 3x + 4
[tex] g(x) = {2}^{x} - 1[/tex]
f(0) = 4
g(0) = 1 - 1 = 0
Which transformation makes 4 = 0?
4 + x = 0 + y
4 - 3 =0 + 1
1 = 1
Option 1 is your answer
Answer:
Option A is the correct answer.
Step-by-step explanation:
y intercept means x value is 0.
f(0) = 3 x 0 + 4 = 4
[tex]g(0)=2^0-1=1-1=0[/tex]
We need same y intercepts
That is f(0) = g(0)
4 + a = 0 + b
Checking all the options
a) f(x) - 3 and g(x) + 1
4 - 3 and 0 + 1
1 and 1
Option A is correct.
b) f(x) + 4 and g(x) - 1
4 + 4 and 0 - 1
8 and -1
Option B is wrong.
c) f(x) - 2 and g(x) + 1
4 - 2 and 0 + 1
2 and 1
Option C is wrong.
d) f(x) + 3 and g(x) - 6
4 + 3 and 0 - 6
7 and -6
Option D is wrong.
So, Option A is the correct answer.